Geology and development of Aguacate mines, Costa Rica - Crespi, R. A. (Universidad de Costa Rica, 2011)
The Aguacate mines are situated on the pacific 18 months, thus giving a through railway from the side of the republic of Costa Rica, in the Aguacate Atlantic to the pacific. Machinery can be delivered mining zone, province of Alajuela, and consist by United Fruit Companyś steamers sailing from of about 1,500 acres. The property is reached by Mobile, New Orleans, New York, Boston, etc., to steamers sailing from Atlantic ports of the United port Limon, and over that companyś railway to States to port Limon, the Costa Rican port of entry San Jose.